2011
DOI: 10.1007/s13410-011-0015-5
|View full text |Cite
|
Sign up to set email alerts
|

Islet cell autoantibodies in patients younger than 20 years of age with recently diagnosed diabetes in Northwest of Iran

Abstract: The presence or absence of islet cell autoantibodies is one of the most direct ways to distinguish between type 1 and 2 diabetic patients. The objective of the present study was to assess the prevalence of β-cell autoantibodies such as glutamic acid decarboxylase-65 antibodies (GADAs) and islet cell antibodies (ICA) among patients younger than 20 years of age with recently diagnosed diabetes in northwest of Iran. From 2006 to 2008, 163 patients were enrolled in this study. They were clinically classified into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In Turkey, Karaguzel et al [31] found that 63% of children with type 1 diabetes at a mean age of 11.7 years and mean duration of 3.4 years were GAD65 autoantibody positive. Marandi et al [32] found that 27.6% of newly diagnosed type 1 diabetes subjects aged under 20 years had antibodies against GAD65, and 94.1% of subjects had a C-peptide of <0.17 nmol/L (<0.50 ng/mL) in a mainly Azeri population in Northwest Iran.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, Karaguzel et al [31] found that 63% of children with type 1 diabetes at a mean age of 11.7 years and mean duration of 3.4 years were GAD65 autoantibody positive. Marandi et al [32] found that 27.6% of newly diagnosed type 1 diabetes subjects aged under 20 years had antibodies against GAD65, and 94.1% of subjects had a C-peptide of <0.17 nmol/L (<0.50 ng/mL) in a mainly Azeri population in Northwest Iran.…”
Section: Discussionmentioning
confidence: 99%